2012
DOI: 10.1681/asn.2011060596
|View full text |Cite
|
Sign up to set email alerts
|

Non-HLA Antibodies to Immunogenic Epitopes Predict the Evolution of Chronic Renal Allograft Injury

Abstract: Chronic allograft injury (CAI) results from a humoral response to mismatches in immunogenic epitopes between the donor and recipient. Although alloantibodies against HLA antigens contribute to the pathogenesis of CAI, alloantibodies against non-HLA antigens likely contribute as well. Here, we used highdensity protein arrays to identify non-HLA antibodies in CAI and subsequently validated a subset in a cohort of 172 serum samples collected serially post-transplantation. There were 38 de novo non-HLA antibodies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
64
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3
1

Relationship

4
6

Authors

Journals

citations
Cited by 80 publications
(65 citation statements)
references
References 54 publications
0
64
1
Order By: Relevance
“…The protein arrays contained approximately 9500 recombinant human proteins expressed as N-terminal GST fusion proteins and spotted on nitrocellulosecoated glass slides. Established protocols (http:// www.invitrogen.com) were followed 24,25 for sample preparation, blocking, probing, drying by centrifugation, scanning, and data acquisition. Slides were scanned using an Axon GenePix 4000B Scanner (Molecular Devices, Sunnyvale, CA) and GenePix pro 6.0 software (Molecular Devices).…”
Section: Protein Microarray Analysesmentioning
confidence: 99%
“…The protein arrays contained approximately 9500 recombinant human proteins expressed as N-terminal GST fusion proteins and spotted on nitrocellulosecoated glass slides. Established protocols (http:// www.invitrogen.com) were followed 24,25 for sample preparation, blocking, probing, drying by centrifugation, scanning, and data acquisition. Slides were scanned using an Axon GenePix 4000B Scanner (Molecular Devices, Sunnyvale, CA) and GenePix pro 6.0 software (Molecular Devices).…”
Section: Protein Microarray Analysesmentioning
confidence: 99%
“…5 Nevertheless, ongoing allograft rejection in HLA identical transplant recipients and patients without detectable anti-HLA Abs to donor HLA antigens (DSA) supports an additional pathogenic role for graft injury by non-HLA antigens, such as protein kinase-z, and MHC class 1-related chain A (MICA). [6][7][8][9] In adult renal transplantation, Terasaki 10 and Terasaki and Cai 11 have shown that preformed and de novo post-transplant production of DSAs correlates with a higher risk of acute rejection (AR) and reduced 1-year graft survival. The impact of the humoral response has not been well studied in the pediatric transplantation.…”
mentioning
confidence: 99%
“…Antibodies to endothelial cell antigens other than HLA antigens have been previously detected in KTRs, particularly in relation to CMV infection. [42][43][44][45] However, because no binding of IgG from nonsensitized sera was found by flow cytometry on IVEC, lysis of these cells with this serum suggests the presence of unknown factors other than IgG able to induce gd T-cell cytolytic potential. This assay could therefore be interesting to identify new factors involved in endothelial cell damage.…”
Section: Discussionmentioning
confidence: 88%